Exploring the Effectiveness of International Knowledge Cooperation: An Analysis of Selected Development Knowledge Actors - Klingebiel, Stephan; Hartmann, Flora L; Madani, Elisa; Paintner, Jonas; Rohe, Rebekka A; Trebs, Lisa; Wolk, Teodor (Springer Nature, 2024)
In this open access book, we provide evidence to support the conceptual discussion of what constitutes “modalities of knowledge interaction” and suggest an analytical framework for effective knowledge cooperation. In practice, knowledge cooperation is realised through different modalities that serve as a toolbox to co-create, share and communicate knowledge among actors. Effective knowledge cooperation is crucial to addressing global challenges. It is increasingly attracting attention due to the rise of South–South Cooperation, to which it is central. Our empirical cases (Germany, India, Republic of Korea and Rwanda) comprise South-South cooperation and traditional development cooperation actors.